Answer:
3x - y = 1
Step-by-step explanation:
The system:
[tex]$\left \{ {{y = 3x -1} \atop {y = 3x + 2}} \right. $[/tex]
There is no solution to this system of equations.
The system:
[tex]$\left \{ {{y = 3x -1} \atop {3x - y = 2}} \right. $[/tex]
[tex]$\left \{ {{y = 3x -1} \atop { y = 3x-2}} \right. $[/tex]
The is one solution to this system.
The system:
[tex]$\left \{ {{y = 3x -1} \atop {3x - y = 1}} \right. $[/tex]
[tex]$\left \{ {{y = 3x -1} \atop { y = 3x-1}} \right. $[/tex]
There are infinity solutions to the system.
The system:
[tex]$\left \{ {{y = 3x -1} \atop {3x + y = 1} \right. $[/tex]
[tex]$\left \{ {{y = 3x -1} \atop { y = 1-3x}} \right. $[/tex]
The is one solution to this system.